Own your morning : reset your A.M. routine to unlock your potential - Plosser, Liz Baker (Hearst Home, 2021)
Plosser believes there's no cookie cutter morning ritual that will lead you to success. Instead she advocates that your AM routine should reflect what matters most to you. Own Your Morning starts with prompts to help you identify your core values: the way you want to spend your energy, time, and resources. Once you've figured out the elements of your personal perfect morning, you'll find insights from wellness experts and personal anecdotes from Liz to help you reimagine your AM habits to benefit your physical and mental health, focus your energy, enhance your productivity, and make the most of your day from the moment you wake up. Includes tips for a killer workout (sweat changes everything!), tap into the power of meditation (Jay Shetty shares his go-to meditation practice), create mini-moments of connectivity with loved ones (such as creating emoji shorthand in your group chat), or fuel your AM awesomeness with a healthy breakfast (including a few recipes!).